iFRAMES DESIGN IN HEALTH SECTOR BLUD: ASSET AND INVENTORY SYSTEM - Satrio Wicaksono Prakoso; Machmudin Eka Prasetya (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This research aims to design an information system to record assets and inventories at DKI Jakarta Regional Public Service Agency (BLUD). This study is based on the findings from Examination Report (LHP) issued by the Indonesian Supreme Audit Institution (BPK RI) which states that there are quite a few problems about assets at BLUD (BPK RI, 2017). This research is expected to answer research questions about how to design the system of assets and inventories needed by BLUD to assist the process of internal control and asset management. This study uses the Framework for the Application of Systems Thinking (FAST) as a method for systems development popularized by Whitten and Bentley (2007). This study uses a case study approach with the triangulation method, where the qualitative data as primary data by conducting interviews and observations. Unit of analysis in this study is the BLUD responsible for asset management. Currently, the existing asset information systems only record fixed assets and not connected to the financial reporting system. Assets and inventories information need to move manually by re-inputting the value to prepare financial statements. The result of this research is a design of asset information system to enhance internal control.Keywords: Assets, Information Systems, Internal Control Systems